2020
DOI: 10.1016/j.amjcard.2020.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Elevated Cardiac Troponin I in Hospitalized Covid-19 Patients

Abstract: This study aimed to determine if cardiac troponin I (cTnI) is an independent predictor of clinical outcomes and whether higher values are associated with worse clinical outcomes in Covid-19 patients. This case-series study was conducted at Phoebe Putney Health System. Participants were confirmed Covid-19 patients admitted to our health system between March 2, 2020 and June 7, 2020. Data were collected from electronic medical records. Patients were divided into 2 groups: with and without elevated cTnI. The cTnI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 12 publications
2
39
1
6
Order By: Relevance
“…A number of investigations seeking to find relevant outcome predictors among hospitalized patients with COVID-19 have shown that, on admission, increased D-dimer concentration 11 and neutrophil-to-lymphocyte ratio 12 as well as enhanced levels of C-reactive protein, 13 creatinine 13 and cardiac troponin I 14 are all associated with a higher risk of intubation. Similarly, a body mass index (BMI) ≥35 kg/m, 15 increasing age, 15 male sex, 15 comorbid status, 13 respiratory rate, 13 and SpO 2 13 have been shown to be independently associated with worse in-hospital outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigations seeking to find relevant outcome predictors among hospitalized patients with COVID-19 have shown that, on admission, increased D-dimer concentration 11 and neutrophil-to-lymphocyte ratio 12 as well as enhanced levels of C-reactive protein, 13 creatinine 13 and cardiac troponin I 14 are all associated with a higher risk of intubation. Similarly, a body mass index (BMI) ≥35 kg/m, 15 increasing age, 15 male sex, 15 comorbid status, 13 respiratory rate, 13 and SpO 2 13 have been shown to be independently associated with worse in-hospital outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…20 studies measured cardiac outcomes on the day of admission [3,29,32,34,35,3741,4348,50-52,57], and one at the time of patient death [33], with the remaining eight studies not specifying the time of assessment [4,36,42,49,5355]. The studies were conducted in 10 countries in four geographical locations (U.S.A. [32,33,41,48,49], the Middle East [34,50,52], Europe [4,3540,44,45,47], and the People’s Republic of China [3,29,42,43,46,51,5357]) with a total of 3553 COVID-19 patients developing cardiac complications and 13,225 COVID-19 patients without cardiac complications. Patients who presented with SARS-CoV-2 associated cardiac complications were, on average, 10 years older than in those who did not (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…As large heterogeneity was detected amongst the total combined study cohort, the cohort was subdivided based on general global region in an attempt to account for this. Cohorts were divided into studies with cohorts primarily situated in the U.S.A [32,33,41,48,49], the Middle East [34,50,52], Europe [4,3540,44,45,47], and China [3,29,42,43,46,51,5357].…”
Section: Resultsmentioning
confidence: 99%
“…Upon retrospective analysis of hs-troponin levels in 523 patients admitted to the hospital with COVID-19 in Italy, Michela et al identified hs-troponin as an independent risk factor for mortality with a hazard ratio (HR) of 1.004 for each 10-point increase in hs-troponin level (P < 0.0001) [ 82 ]. Similarly, Shah et al examined hs-troponin levels in 309 patients admitted to a US hospital with COVID-19 and found a direct correlation between cardiac troponin I (cTnI) levels and need for intubation, dialysis, transfer to the ICU and death [ 7 ]. Arcari et al suggested that both hs-troponin and NP may be particularly useful biomarkers for clinical pneumonia risk stratification [ 6 ].…”
Section: Cardiovascular Prognostic Indicatorsmentioning
confidence: 99%
“…On the opposite end of the spectrum, Szekely et al conducted a systematic echocardiographic study of 100 consecutive patients diagnosed with COVID-19 within 24 h of admission and found that 78% of patients had evidence of cardiac pathology [ 5 ]. Use of biomarkers, such as high-sensitivity troponin (hs-troponin) to detect myocardial injury has resulted in rates somewhere in between, with Arcari et al noting elevation in 38% of 111 patients with COVID-19 admitted to a hospital in Italy [ 6 ], and Shah et al noting elevation in 37.5% of 309 patients with COVID-19 admitted to a hospital in the southern United States [ 7 ]. Rates of cardiac involvement are harder to estimate among individuals with COVID-19 not requiring hospitalization, although a report suggesting myocardial involvement in 46% of 26 competitive college athletes with mild or no symptoms suggests that it may be relatively common even among those who are otherwise young and healthy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%